Cortical hyperexcitability may precede the onset of familial amyotrophic lateral sclerosis - Vucic, Steve; Nicholson, Garth A.; Kiernan, Matthew C. (Brain (London, England : 1878), 2008)
Familial amyotrophic lateral sclerosis (FALS) is an inherited neurodegenerative disorder of the motor neurons. While 10–15% of cases are caused by mutations in the copper/zinc superoxide-dismutase-1 (SOD-1) gene, the dying-forward hypothesis, in which corticomotoneurons induce anterograde excitotoxic motoneuron degeneration, has been proposed as a potential mechanism. The present study applied novel threshold tracking transcranial magnetic stimulation techniques to investigate the mechanisms underlying neurodegeneration in FALS. Studies were undertaken in 14 asymptomatic and 3 pre-symptomatic SOD-1 mutation carriers, followed longitudinally for up to 3-years. The pre-symptomatic subjects were asymptomatic at the time of their initial study but developed symptoms during the follow-up period. Results were compared to 7 SOD-1 FALS patients, 50 sporadic ALS patients and 55 normal controls. Short-interval intracortical inhibition (SICI) was significantly reduced in SOD-1 FALS (−1.2 ± 0.6%) and sporadic ALS patients (−0.7 ± 0.3%) compared to asymptomatic SOD-1 mutation carriers (9.8 ± 1.5%, P<0.00001) and normal controls (8.5 ± 1.0%, P<0.00001). SICI reduction was accompanied by increases in intracortical facilitation, motor evoked potential amplitudes and the slope of the magnetic stimulus-response curve. In two pre-symptomatic SOD-1 mutation carriers SICI was completely absent (SICI patient 1, −3.2%; patients 2, −1.3%), while in one subject there was a 32% reduction in SICI prior to symptom onset. These three individuals subsequently developed clinical features of ALS. Simultaneous investigation of central and peripheral excitability has established that cortical hyperexcitability develops in clinically affected SOD-1 FALS patients, similar to that seen in sporadic ALS patients, thereby suggesting that a similar pathophysiological process in evident in both familial and sporadic ALS patients. In addition, the present study has established that cortical hyperexcitability precedes the development of clinical symptoms in pre-symptomatic carriers of the SOD1 mutation, thereby suggesting that cortical hyperexcitability underlies neurodegeneration in FALS.